Sini san regulates intestinal flora and short-chain fatty acids to ameliorate hepatocyte apoptosis and relieve CCl4-induced liver fibrosis in mice - Wu, Qiong; Zhu, Fangsi; Yao, Yu; Chen, Luyun; Ding, Yijie; Su, Yong; Ge, Chaoliang (Frontiers in Pharmacology, 2024)
Sini-san (SNS), a traditional Chinese medicine, is effective in treating liver fibrosis with an unclear mechanism. While disturbance of intestinal flora and the subsequent secretion of short-chain fatty acids (SCFAs) is suggested to be involved in the progression of liver fibrosis, whether SNS produces the anti-fibrosis effect through the regulation of intestinal flora and SCFAs remains unclear. In the current study, carbon tetrachloride (CCl4) treated mice were dosed with SNS to examine the anti-fibrosis effect and the involved mechanism. Biochemical parameters, histological staining and analyses of fibrotic gene expression were used to evaluate the anti-fibrosis effect of SNS, while intestinal flora and SCFAs content were determined by 16S rRNA and LC-MS to evaluate the mechanism. In vivo results showed that SNS improved liver function, reduced hepatocyte apoptosis and FFAR2/3 expression, and restored intestinal dysbiosis and reduced PA, BA and IsA levels. In vitro experiments showed that PA, BA and IsA exacerbated TNF-α-induced HepG2 apoptosis. Notably, the protective effects of SNS were compromised in pseudo-sterile mice. In conclusion, our experimental results suggest that disturbance in intestinal flora results in elevated SCFAs, which further exacerbates hepatocyte apoptosis in liver fibrosis, while SNS suppresses CCl4-induced liver fibrosis at least partially by reinstating intestinal flora homeostasis and reducing SCFAs levels.